KONVERGENSI HUKUM ADMINISTRASI NEGARA: ANALISIS TERHADAP KEPUTUSAN TATA USAHA NEGARA YANG MENGANDUNG UNSUR HUKUM PERDATA - Pantja Astawa, I Gde (Faculty of Law, Universitas Pasundan, 2024)
The State Administrative Decision (KTUN) plays a central role in regulating the relationship between the government and society. However, the exclusion of KTUN classified as a civil legal action, as stipulated in Article 2 letter a of Law No. 5 of 1986 concerning the State Administrative Court, has created ambiguity and the potential for overlapping jurisdiction between the State Administrative Court (PTUN) and the General Court. This study aims to analyze the convergence of administrative law and private law within the context of KTUN and provide recommendations for resolving the contradictions in the existing legal framework. This research employs a normative legal method, utilizing both statutory and conceptual approaches, and analyzes data from regulations and court decisions. The findings reveal that the terminological confusion within the State Administrative Court Law causes legal uncertainty and overlapping jurisdiction between the PTUN and general courts. The implications of this study highlight the need for revising the PTUN Law to eliminate the exclusion of State Administrative Decree involving private law elements, along with improving the competence of judges in handling disputes that involve the convergence of administrative and private law.